Nove kulturne tehnologije, komodifikacija kulture in študije občinstva - Luthar, Breda (Teorija in praksa, 2010)
The article engages with the question of whether the everydayness of new media and growing media convergence on one hand, and contemporary cultural production and distribution that is characterized by the increasing commodification of culture and promotional framing of cultural artefacts on the other, require a rethinking of audience studies. It argues that new and old media are not only consumed as texts, but are embodied and embedded in our everyday life as material sensory objects, and are constantly part of our social and private environment. The author argues that, in order to assess the social "effects" of new media, these changes require a more systematic investigation of the prothetic and sensoric role of the media, and demand a rethinking of the marginalised tradition within communication research represented by authors like Innis and McLuhan and studies of material culture in general. Secondly, it argues that the important change in contemporary cultural production is the economisation of culture and the promotional prefiguration of cultural texts. Through framing practices, texts are contextualised and semantically extended and should therefore not be treated as self-contained aesthetic artefacts. In closing, the article explores how the semantic extension of a text should be addressed in the context of studies of media reception.
Keywords: Mass media; Množični mediji; New technologies; Nove tehnologije; Culture; Kultura; Občinstvo; Audience; medijske študije